Determinants of FDI in Developing Countries: Has Globalization Changed the Rules of the Game? - Peter Nunnenkamp; Julius Spatz (Transnational Corporations, 2002)
There is a startling gap between current thinking on, allegedly, globalization-induced changes in international competition for foreign direct investment (FDI) and the lack of recent empirical evidence on shifts in the relative importance of traditional and non-traditional determinants of FDI in developing countries. We attempt to narrow this gap by making use of comprehensive survey data, collected by the European Round Table of Industrialists, on investment conditions in 28 developing countries since the late 1980s. Applying Spearman correlation coefficients and panel-data regression models, we show that surprisingly little has changed so far. Traditional market-related determinants are still dominant factors shaping the distribution of FDI. If at all, the importance of non-traditional FDI determinants has increased only modestly.
Keywords: F21; 330; Direktinvestition; Globalisierung; Entwicklungsländer